--- a/src/HOL/OrderedGroup.thy Mon Feb 08 14:06:48 2010 +0100
+++ b/src/HOL/OrderedGroup.thy Mon Feb 08 14:06:51 2010 +0100
@@ -710,7 +710,7 @@
subclass linordered_cancel_ab_semigroup_add ..
-lemma neg_less_eq_nonneg:
+lemma neg_less_eq_nonneg [simp]:
"- a \<le> a \<longleftrightarrow> 0 \<le> a"
proof
assume A: "- a \<le> a" show "0 \<le> a"
@@ -728,8 +728,27 @@
show "0 \<le> a" using A .
qed
qed
-
-lemma less_eq_neg_nonpos:
+
+lemma neg_less_nonneg [simp]:
+ "- a < a \<longleftrightarrow> 0 < a"
+proof
+ assume A: "- a < a" show "0 < a"
+ proof (rule classical)
+ assume "\<not> 0 < a"
+ then have "a \<le> 0" by auto
+ with A have "- a < 0" by (rule less_le_trans)
+ then show ?thesis by auto
+ qed
+next
+ assume A: "0 < a" show "- a < a"
+ proof (rule less_trans)
+ show "- a < 0" using A by (simp add: minus_le_iff)
+ next
+ show "0 < a" using A .
+ qed
+qed
+
+lemma less_eq_neg_nonpos [simp]:
"a \<le> - a \<longleftrightarrow> a \<le> 0"
proof
assume A: "a \<le> - a" show "a \<le> 0"
@@ -748,7 +767,7 @@
qed
qed
-lemma equal_neg_zero:
+lemma equal_neg_zero [simp]:
"a = - a \<longleftrightarrow> a = 0"
proof
assume "a = 0" then show "a = - a" by simp
@@ -765,9 +784,81 @@
qed
qed
-lemma neg_equal_zero:
+lemma neg_equal_zero [simp]:
"- a = a \<longleftrightarrow> a = 0"
- unfolding equal_neg_zero [symmetric] by auto
+ by (auto dest: sym)
+
+lemma double_zero [simp]:
+ "a + a = 0 \<longleftrightarrow> a = 0"
+proof
+ assume assm: "a + a = 0"
+ then have a: "- a = a" by (rule minus_unique)
+ then show "a = 0" by (simp add: neg_equal_zero)
+qed simp
+
+lemma double_zero_sym [simp]:
+ "0 = a + a \<longleftrightarrow> a = 0"
+ by (rule, drule sym) simp_all
+
+lemma zero_less_double_add_iff_zero_less_single_add [simp]:
+ "0 < a + a \<longleftrightarrow> 0 < a"
+proof
+ assume "0 < a + a"
+ then have "0 - a < a" by (simp only: diff_less_eq)
+ then have "- a < a" by simp
+ then show "0 < a" by (simp add: neg_less_nonneg)
+next
+ assume "0 < a"
+ with this have "0 + 0 < a + a"
+ by (rule add_strict_mono)
+ then show "0 < a + a" by simp
+qed
+
+lemma zero_le_double_add_iff_zero_le_single_add [simp]:
+ "0 \<le> a + a \<longleftrightarrow> 0 \<le> a"
+ by (auto simp add: le_less)
+
+lemma double_add_less_zero_iff_single_add_less_zero [simp]:
+ "a + a < 0 \<longleftrightarrow> a < 0"
+proof -
+ have "\<not> a + a < 0 \<longleftrightarrow> \<not> a < 0"
+ by (simp add: not_less)
+ then show ?thesis by simp
+qed
+
+lemma double_add_le_zero_iff_single_add_le_zero [simp]:
+ "a + a \<le> 0 \<longleftrightarrow> a \<le> 0"
+proof -
+ have "\<not> a + a \<le> 0 \<longleftrightarrow> \<not> a \<le> 0"
+ by (simp add: not_le)
+ then show ?thesis by simp
+qed
+
+lemma le_minus_self_iff:
+ "a \<le> - a \<longleftrightarrow> a \<le> 0"
+proof -
+ from add_le_cancel_left [of "- a" "a + a" 0]
+ have "a \<le> - a \<longleftrightarrow> a + a \<le> 0"
+ by (simp add: add_assoc [symmetric])
+ thus ?thesis by simp
+qed
+
+lemma minus_le_self_iff:
+ "- a \<le> a \<longleftrightarrow> 0 \<le> a"
+proof -
+ from add_le_cancel_left [of "- a" 0 "a + a"]
+ have "- a \<le> a \<longleftrightarrow> 0 \<le> a + a"
+ by (simp add: add_assoc [symmetric])
+ thus ?thesis by simp
+qed
+
+lemma minus_max_eq_min:
+ "- max x y = min (-x) (-y)"
+ by (auto simp add: max_def min_def)
+
+lemma minus_min_eq_max:
+ "- min x y = max (-x) (-y)"
+ by (auto simp add: max_def min_def)
end
@@ -941,375 +1032,6 @@
end
-
-subsection {* Lattice Ordered (Abelian) Groups *}
-
-class semilattice_inf_ab_group_add = ordered_ab_group_add + semilattice_inf
-begin
-
-lemma add_inf_distrib_left:
- "a + inf b c = inf (a + b) (a + c)"
-apply (rule antisym)
-apply (simp_all add: le_infI)
-apply (rule add_le_imp_le_left [of "uminus a"])
-apply (simp only: add_assoc [symmetric], simp)
-apply rule
-apply (rule add_le_imp_le_left[of "a"], simp only: add_assoc[symmetric], simp)+
-done
-
-lemma add_inf_distrib_right:
- "inf a b + c = inf (a + c) (b + c)"
-proof -
- have "c + inf a b = inf (c+a) (c+b)" by (simp add: add_inf_distrib_left)
- thus ?thesis by (simp add: add_commute)
-qed
-
-end
-
-class semilattice_sup_ab_group_add = ordered_ab_group_add + semilattice_sup
-begin
-
-lemma add_sup_distrib_left:
- "a + sup b c = sup (a + b) (a + c)"
-apply (rule antisym)
-apply (rule add_le_imp_le_left [of "uminus a"])
-apply (simp only: add_assoc[symmetric], simp)
-apply rule
-apply (rule add_le_imp_le_left [of "a"], simp only: add_assoc[symmetric], simp)+
-apply (rule le_supI)
-apply (simp_all)
-done
-
-lemma add_sup_distrib_right:
- "sup a b + c = sup (a+c) (b+c)"
-proof -
- have "c + sup a b = sup (c+a) (c+b)" by (simp add: add_sup_distrib_left)
- thus ?thesis by (simp add: add_commute)
-qed
-
-end
-
-class lattice_ab_group_add = ordered_ab_group_add + lattice
-begin
-
-subclass semilattice_inf_ab_group_add ..
-subclass semilattice_sup_ab_group_add ..
-
-lemmas add_sup_inf_distribs = add_inf_distrib_right add_inf_distrib_left add_sup_distrib_right add_sup_distrib_left
-
-lemma inf_eq_neg_sup: "inf a b = - sup (-a) (-b)"
-proof (rule inf_unique)
- fix a b :: 'a
- show "- sup (-a) (-b) \<le> a"
- by (rule add_le_imp_le_right [of _ "sup (uminus a) (uminus b)"])
- (simp, simp add: add_sup_distrib_left)
-next
- fix a b :: 'a
- show "- sup (-a) (-b) \<le> b"
- by (rule add_le_imp_le_right [of _ "sup (uminus a) (uminus b)"])
- (simp, simp add: add_sup_distrib_left)
-next
- fix a b c :: 'a
- assume "a \<le> b" "a \<le> c"
- then show "a \<le> - sup (-b) (-c)" by (subst neg_le_iff_le [symmetric])
- (simp add: le_supI)
-qed
-
-lemma sup_eq_neg_inf: "sup a b = - inf (-a) (-b)"
-proof (rule sup_unique)
- fix a b :: 'a
- show "a \<le> - inf (-a) (-b)"
- by (rule add_le_imp_le_right [of _ "inf (uminus a) (uminus b)"])
- (simp, simp add: add_inf_distrib_left)
-next
- fix a b :: 'a
- show "b \<le> - inf (-a) (-b)"
- by (rule add_le_imp_le_right [of _ "inf (uminus a) (uminus b)"])
- (simp, simp add: add_inf_distrib_left)
-next
- fix a b c :: 'a
- assume "a \<le> c" "b \<le> c"
- then show "- inf (-a) (-b) \<le> c" by (subst neg_le_iff_le [symmetric])
- (simp add: le_infI)
-qed
-
-lemma neg_inf_eq_sup: "- inf a b = sup (-a) (-b)"
-by (simp add: inf_eq_neg_sup)
-
-lemma neg_sup_eq_inf: "- sup a b = inf (-a) (-b)"
-by (simp add: sup_eq_neg_inf)
-
-lemma add_eq_inf_sup: "a + b = sup a b + inf a b"
-proof -
- have "0 = - inf 0 (a-b) + inf (a-b) 0" by (simp add: inf_commute)
- hence "0 = sup 0 (b-a) + inf (a-b) 0" by (simp add: inf_eq_neg_sup)
- hence "0 = (-a + sup a b) + (inf a b + (-b))"
- by (simp add: add_sup_distrib_left add_inf_distrib_right)
- (simp add: algebra_simps)
- thus ?thesis by (simp add: algebra_simps)
-qed
-
-subsection {* Positive Part, Negative Part, Absolute Value *}
-
-definition
- nprt :: "'a \<Rightarrow> 'a" where
- "nprt x = inf x 0"
-
-definition
- pprt :: "'a \<Rightarrow> 'a" where
- "pprt x = sup x 0"
-
-lemma pprt_neg: "pprt (- x) = - nprt x"
-proof -
- have "sup (- x) 0 = sup (- x) (- 0)" unfolding minus_zero ..
- also have "\<dots> = - inf x 0" unfolding neg_inf_eq_sup ..
- finally have "sup (- x) 0 = - inf x 0" .
- then show ?thesis unfolding pprt_def nprt_def .
-qed
-
-lemma nprt_neg: "nprt (- x) = - pprt x"
-proof -
- from pprt_neg have "pprt (- (- x)) = - nprt (- x)" .
- then have "pprt x = - nprt (- x)" by simp
- then show ?thesis by simp
-qed
-
-lemma prts: "a = pprt a + nprt a"
-by (simp add: pprt_def nprt_def add_eq_inf_sup[symmetric])
-
-lemma zero_le_pprt[simp]: "0 \<le> pprt a"
-by (simp add: pprt_def)
-
-lemma nprt_le_zero[simp]: "nprt a \<le> 0"
-by (simp add: nprt_def)
-
-lemma le_eq_neg: "a \<le> - b \<longleftrightarrow> a + b \<le> 0" (is "?l = ?r")
-proof -
- have a: "?l \<longrightarrow> ?r"
- apply (auto)
- apply (rule add_le_imp_le_right[of _ "uminus b" _])
- apply (simp add: add_assoc)
- done
- have b: "?r \<longrightarrow> ?l"
- apply (auto)
- apply (rule add_le_imp_le_right[of _ "b" _])
- apply (simp)
- done
- from a b show ?thesis by blast
-qed
-
-lemma pprt_0[simp]: "pprt 0 = 0" by (simp add: pprt_def)
-lemma nprt_0[simp]: "nprt 0 = 0" by (simp add: nprt_def)
-
-lemma pprt_eq_id [simp, noatp]: "0 \<le> x \<Longrightarrow> pprt x = x"
- by (simp add: pprt_def sup_aci sup_absorb1)
-
-lemma nprt_eq_id [simp, noatp]: "x \<le> 0 \<Longrightarrow> nprt x = x"
- by (simp add: nprt_def inf_aci inf_absorb1)
-
-lemma pprt_eq_0 [simp, noatp]: "x \<le> 0 \<Longrightarrow> pprt x = 0"
- by (simp add: pprt_def sup_aci sup_absorb2)
-
-lemma nprt_eq_0 [simp, noatp]: "0 \<le> x \<Longrightarrow> nprt x = 0"
- by (simp add: nprt_def inf_aci inf_absorb2)
-
-lemma sup_0_imp_0: "sup a (- a) = 0 \<Longrightarrow> a = 0"
-proof -
- {
- fix a::'a
- assume hyp: "sup a (-a) = 0"
- hence "sup a (-a) + a = a" by (simp)
- hence "sup (a+a) 0 = a" by (simp add: add_sup_distrib_right)
- hence "sup (a+a) 0 <= a" by (simp)
- hence "0 <= a" by (blast intro: order_trans inf_sup_ord)
- }
- note p = this
- assume hyp:"sup a (-a) = 0"
- hence hyp2:"sup (-a) (-(-a)) = 0" by (simp add: sup_commute)
- from p[OF hyp] p[OF hyp2] show "a = 0" by simp
-qed
-
-lemma inf_0_imp_0: "inf a (-a) = 0 \<Longrightarrow> a = 0"
-apply (simp add: inf_eq_neg_sup)
-apply (simp add: sup_commute)
-apply (erule sup_0_imp_0)
-done
-
-lemma inf_0_eq_0 [simp, noatp]: "inf a (- a) = 0 \<longleftrightarrow> a = 0"
-by (rule, erule inf_0_imp_0) simp
-
-lemma sup_0_eq_0 [simp, noatp]: "sup a (- a) = 0 \<longleftrightarrow> a = 0"
-by (rule, erule sup_0_imp_0) simp
-
-lemma zero_le_double_add_iff_zero_le_single_add [simp]:
- "0 \<le> a + a \<longleftrightarrow> 0 \<le> a"
-proof
- assume "0 <= a + a"
- hence a:"inf (a+a) 0 = 0" by (simp add: inf_commute inf_absorb1)
- have "(inf a 0)+(inf a 0) = inf (inf (a+a) 0) a" (is "?l=_")
- by (simp add: add_sup_inf_distribs inf_aci)
- hence "?l = 0 + inf a 0" by (simp add: a, simp add: inf_commute)
- hence "inf a 0 = 0" by (simp only: add_right_cancel)
- then show "0 <= a" unfolding le_iff_inf by (simp add: inf_commute)
-next
- assume a: "0 <= a"
- show "0 <= a + a" by (simp add: add_mono[OF a a, simplified])
-qed
-
-lemma double_zero: "a + a = 0 \<longleftrightarrow> a = 0"
-proof
- assume assm: "a + a = 0"
- then have "a + a + - a = - a" by simp
- then have "a + (a + - a) = - a" by (simp only: add_assoc)
- then have a: "- a = a" by simp
- show "a = 0" apply (rule antisym)
- apply (unfold neg_le_iff_le [symmetric, of a])
- unfolding a apply simp
- unfolding zero_le_double_add_iff_zero_le_single_add [symmetric, of a]
- unfolding assm unfolding le_less apply simp_all done
-next
- assume "a = 0" then show "a + a = 0" by simp
-qed
-
-lemma zero_less_double_add_iff_zero_less_single_add:
- "0 < a + a \<longleftrightarrow> 0 < a"
-proof (cases "a = 0")
- case True then show ?thesis by auto
-next
- case False then show ?thesis (*FIXME tune proof*)
- unfolding less_le apply simp apply rule
- apply clarify
- apply rule
- apply assumption
- apply (rule notI)
- unfolding double_zero [symmetric, of a] apply simp
- done
-qed
-
-lemma double_add_le_zero_iff_single_add_le_zero [simp]:
- "a + a \<le> 0 \<longleftrightarrow> a \<le> 0"
-proof -
- have "a + a \<le> 0 \<longleftrightarrow> 0 \<le> - (a + a)" by (subst le_minus_iff, simp)
- moreover have "\<dots> \<longleftrightarrow> a \<le> 0" by (simp add: zero_le_double_add_iff_zero_le_single_add)
- ultimately show ?thesis by blast
-qed
-
-lemma double_add_less_zero_iff_single_less_zero [simp]:
- "a + a < 0 \<longleftrightarrow> a < 0"
-proof -
- have "a + a < 0 \<longleftrightarrow> 0 < - (a + a)" by (subst less_minus_iff, simp)
- moreover have "\<dots> \<longleftrightarrow> a < 0" by (simp add: zero_less_double_add_iff_zero_less_single_add)
- ultimately show ?thesis by blast
-qed
-
-declare neg_inf_eq_sup [simp] neg_sup_eq_inf [simp]
-
-lemma le_minus_self_iff: "a \<le> - a \<longleftrightarrow> a \<le> 0"
-proof -
- from add_le_cancel_left [of "uminus a" "plus a a" zero]
- have "(a <= -a) = (a+a <= 0)"
- by (simp add: add_assoc[symmetric])
- thus ?thesis by simp
-qed
-
-lemma minus_le_self_iff: "- a \<le> a \<longleftrightarrow> 0 \<le> a"
-proof -
- from add_le_cancel_left [of "uminus a" zero "plus a a"]
- have "(-a <= a) = (0 <= a+a)"
- by (simp add: add_assoc[symmetric])
- thus ?thesis by simp
-qed
-
-lemma zero_le_iff_zero_nprt: "0 \<le> a \<longleftrightarrow> nprt a = 0"
-unfolding le_iff_inf by (simp add: nprt_def inf_commute)
-
-lemma le_zero_iff_zero_pprt: "a \<le> 0 \<longleftrightarrow> pprt a = 0"
-unfolding le_iff_sup by (simp add: pprt_def sup_commute)
-
-lemma le_zero_iff_pprt_id: "0 \<le> a \<longleftrightarrow> pprt a = a"
-unfolding le_iff_sup by (simp add: pprt_def sup_commute)
-
-lemma zero_le_iff_nprt_id: "a \<le> 0 \<longleftrightarrow> nprt a = a"
-unfolding le_iff_inf by (simp add: nprt_def inf_commute)
-
-lemma pprt_mono [simp, noatp]: "a \<le> b \<Longrightarrow> pprt a \<le> pprt b"
-unfolding le_iff_sup by (simp add: pprt_def sup_aci sup_assoc [symmetric, of a])
-
-lemma nprt_mono [simp, noatp]: "a \<le> b \<Longrightarrow> nprt a \<le> nprt b"
-unfolding le_iff_inf by (simp add: nprt_def inf_aci inf_assoc [symmetric, of a])
-
-end
-
-lemmas add_sup_inf_distribs = add_inf_distrib_right add_inf_distrib_left add_sup_distrib_right add_sup_distrib_left
-
-
-class lattice_ab_group_add_abs = lattice_ab_group_add + abs +
- assumes abs_lattice: "\<bar>a\<bar> = sup a (- a)"
-begin
-
-lemma abs_prts: "\<bar>a\<bar> = pprt a - nprt a"
-proof -
- have "0 \<le> \<bar>a\<bar>"
- proof -
- have a: "a \<le> \<bar>a\<bar>" and b: "- a \<le> \<bar>a\<bar>" by (auto simp add: abs_lattice)
- show ?thesis by (rule add_mono [OF a b, simplified])
- qed
- then have "0 \<le> sup a (- a)" unfolding abs_lattice .
- then have "sup (sup a (- a)) 0 = sup a (- a)" by (rule sup_absorb1)
- then show ?thesis
- by (simp add: add_sup_inf_distribs sup_aci
- pprt_def nprt_def diff_minus abs_lattice)
-qed
-
-subclass ordered_ab_group_add_abs
-proof
- have abs_ge_zero [simp]: "\<And>a. 0 \<le> \<bar>a\<bar>"
- proof -
- fix a b
- have a: "a \<le> \<bar>a\<bar>" and b: "- a \<le> \<bar>a\<bar>" by (auto simp add: abs_lattice)
- show "0 \<le> \<bar>a\<bar>" by (rule add_mono [OF a b, simplified])
- qed
- have abs_leI: "\<And>a b. a \<le> b \<Longrightarrow> - a \<le> b \<Longrightarrow> \<bar>a\<bar> \<le> b"
- by (simp add: abs_lattice le_supI)
- fix a b
- show "0 \<le> \<bar>a\<bar>" by simp
- show "a \<le> \<bar>a\<bar>"
- by (auto simp add: abs_lattice)
- show "\<bar>-a\<bar> = \<bar>a\<bar>"
- by (simp add: abs_lattice sup_commute)
- show "a \<le> b \<Longrightarrow> - a \<le> b \<Longrightarrow> \<bar>a\<bar> \<le> b" by (fact abs_leI)
- show "\<bar>a + b\<bar> \<le> \<bar>a\<bar> + \<bar>b\<bar>"
- proof -
- have g:"abs a + abs b = sup (a+b) (sup (-a-b) (sup (-a+b) (a + (-b))))" (is "_=sup ?m ?n")
- by (simp add: abs_lattice add_sup_inf_distribs sup_aci diff_minus)
- have a:"a+b <= sup ?m ?n" by (simp)
- have b:"-a-b <= ?n" by (simp)
- have c:"?n <= sup ?m ?n" by (simp)
- from b c have d: "-a-b <= sup ?m ?n" by(rule order_trans)
- have e:"-a-b = -(a+b)" by (simp add: diff_minus)
- from a d e have "abs(a+b) <= sup ?m ?n"
- by (drule_tac abs_leI, auto)
- with g[symmetric] show ?thesis by simp
- qed
-qed
-
-end
-
-lemma sup_eq_if:
- fixes a :: "'a\<Colon>{lattice_ab_group_add, linorder}"
- shows "sup a (- a) = (if a < 0 then - a else a)"
-proof -
- note add_le_cancel_right [of a a "- a", symmetric, simplified]
- moreover note add_le_cancel_right [of "-a" a a, symmetric, simplified]
- then show ?thesis by (auto simp: sup_max min_max.sup_absorb1 min_max.sup_absorb2)
-qed
-
-lemma abs_if_lattice:
- fixes a :: "'a\<Colon>{lattice_ab_group_add_abs, linorder}"
- shows "\<bar>a\<bar> = (if a < 0 then - a else a)"
-by auto
-
-
text {* Needed for abelian cancellation simprocs: *}
lemma add_cancel_21: "((x::'a::ab_group_add) + (y + z) = y + u) = (x + z = u)"
@@ -1346,14 +1068,6 @@
apply (simp_all add: prems)
done
-lemma estimate_by_abs:
- "a + b <= (c::'a::lattice_ab_group_add_abs) \<Longrightarrow> a <= c + abs b"
-proof -
- assume "a+b <= c"
- hence 2: "a <= c+(-b)" by (simp add: algebra_simps)
- have 3: "(-b) <= abs b" by (rule abs_ge_minus_self)
- show ?thesis by (rule le_add_right_mono[OF 2 3])
-qed
subsection {* Tools setup *}